B. x = f(y) = 7 + y
C. y = f(x) = 7x
D. y = f(x) = y – 7
E. y = f(x) = 7 + y
Answer: The equation could model a scenario determining the number of players on each team in a league of five teams, if 2 players have to be taken out of the possible players to be referees and to keep score. There will be 11 players on each team.
Step-by-step explanation: Hope this helped you in any way :D
The equation x/5 - 2 = 11 could describe a scenario in a new basketball league. Here, x is the total number of basketball players signed up, 5 is the number of players on a team, '-2' stands for the administrative team and '11' is the number of teams remaining after removing the administrative team.
The equation given is x/5 - 2 = 11. To make this represent a basketball scenario, the most direct interpretation would be this: suppose the 'x' represents the total number of basketball players that have signed up for a new league. The '5' could represent the number of players on a team and the '2' subtracted from the equation could be an administrative team that doesn't play but are necessary to manage the league.
So, in this scenario, x/5 would represent the quantity of teams you could form with the players that have signed up. The '-2' represents the removal of the administrative team and the '11' is the leftover teams after you have removed the administrative team.
This scenario would then imply that, with the total number of players and if you remove the administrative team, there should be 11 teams left in the league.
#SPJ2
How much time does Dave spend on the stationary bicycle in a week?
A.
the total number of hours Dave spends on the stationary bicycle each visit
B.
the total number of hours Dave spends on the treadmill each month
C.
the total number of times Dave spent exercising in 10 weeks
Unsubscribe · Report · Sun Mathematics
Answer:
x = - 1
Step-by-step explanation:
= 2x + 1 ( multiply both sides by 5 to clear the fraction )
4x - 1 = 5(2x + 1) ← distribute parenthesis
4x - 1 = 10x + 5 ( subtract 10x from both sides )
- 6x - 1 = 5 ( add 1 to both sides )
- 6x = 6 ( divide both sides by - 6 )
x = - 1
(4b - 3)/(2a) -1